Gambaran Kecemasan Pada Lanjut Usia Dengan Penderita Diabetes Melitus Di Posyandu Desa Praon Nusukan Surakarta - Mustaqim, Muh Firman; , Arum Pratiwi, S.Kp., M.Kes (2016)
In the world of health, diabetes mellitus, including diseases there are not contagiuous, but it is one of the chronic degenerative diseases. Diabetes mellitus is a medical disorder end a collection of symptoms caused by elevated blood sugar levels due to deficiency or insulin resistance, as well as the complications of acute and chronic. This study aimed to describe the anxiety in elderly patients with diabetes Mellitus in the village of Posyandu Praon Nusukan Surakarta. This research study using the method of diskriptif approach with cross sectional analytic. This research was conducted in doing in the Village Elderly Posyandu Praon Nusukan Surakarta in April 2016. Data collection methods used are questionnaire and documentation. The population in this research totalling 33 people, the sample in this study amounted to 30 people. The sample in this research is the elderly elderly posyandu coming and recorded in the village of Nusukan who have a history of Praon diabetes mellitus. Engineering samples used in the study was the accidental sampling. Data analysis techniques using descriptive test. The results of this research show the characteristics of the respondents aged between 60-69 years i.e. as many as 18 people (60.0%) and the smallest is older than 70 years i.e. as many as 12 people (40,0%) and at the kateogori level of anxiety showed most respondents included no anxious i.e. as many as 17 people (57,7%), but that included as many as 13 people anxious (43.3%). The majority of elderly people with diabetes mellitus in aged between 60-69 years old, educated, women-sex basis, and do not work with the level of anxiety as much as 13 people (43.3%) and not worry as much as 17 persons (56.7%).